Virtual Tour Design In Egypt Building Darussalam Gontor Putri University - Indah Putri Arosi; Faisal Reza Pradhana; Dihin Muriyatmoko (Procedia of Engineering and Life Science, 2021)
University of Darussalam Gontor already have media brochures, video profil and social media as publicity and advertising tools. But now in the area of technology 4.0, the media are rated not enough, where people need a media where they can interact directly in it. The research is aimed to build a media interaction of the campus interactive based model of three dimensions by using the technology of virtual reality. Virtual Reality is considered able to deliver information in a more effective due to its ability to reach the sense of human beings, good eyesight, hearing, and touch trough interaction in real time. Data retrieved trough the stages of observation of the building as directly as well as through taking sample of photos and videos. An android based mobile application by implementing the first-person shooter (FPS) method to its user and designed to follow the ADDIE development model. In the future, it is hoped that the VR campus tour application can be used in multiplayer to get a fun group campus tour experience.